A case of EBV encephalomyelitis with positive anti-GFAP-IgG antibody with recurrent fever and dysuresia as the main symptoms: Case report and retrospective analysis. Issue 48 (2nd December 2022) - Wang, Lulu; Dong, Lulu; Zhao, Mingmin; Jiang, Chao; Geng, Minxia; Li, Shuang; Xing, Jiahao; Wang, Tianjun
Abstract : Rationale: Due to neuronal destruction caused by Epstein-Barr virus (EBV) infection, exposure to neuronal surface antigens may lead to an imbalance in immune tolerance, which in turn triggers an autoimmune response. In addition, due to the involvement of nonspecific B-cell activation or molecular mimicry, EBV and Glial Fibrillary Acidic Protein (GFAP) receptors may have common epitopes. Viral infection triggers activation of B-cell and cross-reaction with viral antibodies, resulting in autoimmune encephalomyelitis. The clinical presentation may be complex or even atypical. A small number of patients may develop autoimmune reactions. Patient concerns: Most patients with EBV encephalomyelitis have a good prognosis, with the disease generally having a short course, few complications, and a good prognosis. In most patients, after treatment, their neurological function basically recovers within a few weeks or months. Diagnosis interventions: The patient had fever and headache. His 3 tests for cerebral spinal fluid (CSF) are consistent with the features of viral encephalomyelitis. Pathogenic examination of CSF confirmed EBV, and imaging suggested brain and spinal cord involvement. After antiviral treatment, the patient's symptoms relieved. The diagnosis of EBV encephalomyelitis was considered. However, the patient's temperature continued to increase. He was transferred to a superior hospital and was given GFAP-Ab in CSF, which was strongly positive. The patient was given immunoglobulin and antiviral therapy. This supports the diagnosis of GFAP-IgG antibody positive with EBV encephalomyelitis. Outcomes: After treatment with antiviral drugs and immunoglobulins, the patient's symptoms improved and he was able to function. Lessons: EBV encephalomyelitis is a rare clinical disease. Therefore, more attention should be paid to the early diagnosis and treatment of similar patients to avoid misdiagnosis. CSF tests, genetic tests, and imaging tests can confirm the diagnosis.